On mooring line tension and fatigue prediction for offshore vertical axis wind turbines: A comparison of lumped mass and quasi-static approaches - Cevasco, Debora; Collu, Maurizio; Rizzo, C. M.; Hall, M. (SAGE, 2018)
Despite several potential advantages, relatively few studies and design support tools have been developed for floating vertical axis wind turbines. Due to the substantial aerodynamics differences, the analyses of vertical axis wind turbine on floating structures cannot be easily extended from what have been already done for horizontal axis wind turbines. Therefore, the main aim of the present work is to compare the dynamic response of the floating offshore wind turbine system adopting two different mooring dynamics approaches. Two versions of the in-house aero-hydro-mooring coupled model of dynamics for floating vertical axis wind turbine (FloVAWT) have been used, employing a mooring quasi-static model, which solves the equations using an energetic approach, and a modified version of floating vertical axis wind turbine, which instead couples with the lumped mass mooring line model MoorDyn. The results, in terms of mooring line tension, fatigue and response in frequency have been obtained and analysed, based on a 5 MW Darrieus type rotor supported by the OC4-DeepCwind semisubmersible.
Keywords: Floating vertical axis wind turbine; mooring dynamics; coupled dynamics; mooring line tension